Architecture and Time—Time in Architecture - Libor Monhart (Oz, 1998)
Time is a physical quantity that has perpetually challenged humankind. A meter will always be a meter, and a kilo a kilo, but time can in many ways be interpreted as a relative term. In our contemporary world, many common devices are intricately related to time; the computer, the radio, the phone, and the television for example.